Comparison of six commercial human T-cell lymphotropic virus type I (HTLV-I) enzyme immunoassay kits for detection of antibody to HTLV-I and -II. - Cossen, C (1992)
Three licensed and three research human T-cell lymphotropic virus type I (HTLV-I) enzyme immunoassay (EIA) kits were evaluated with a panel of 213 serum or plasma samples which were previously tested by the indirect immunofluorescence method for HTLV-I and -II antibodies. The three research kits were found to be more sensitive and specific than the three licensed kits.